2018
DOI: 10.1002/ejsp.2345
|View full text |Cite
|
Sign up to set email alerts
|

What makes displaced revenge taste sweet: Retributing displaced responsibility or sending a message to the original perpetrator?

Abstract: The present research investigates the psychological dynamics underlying displaced revenge. We examine (1) the effect of entitativity on displaced revenge tendencies, including potential mediators of this effect, and (2) the conditions under which taking displaced revenge is satisfying for avengers. In three studies, we show that (a) perpetrator group entitativity predicts the tendency to take displaced revenge via perceptions that the vengeful action is effective in delivering a message to the original perpetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Our findings extend the literature on displaced revenge (Sjöström et al, 2018;Strenstrom et al, 2008) in several ways. First, they show that group-directed displaced revenge occurs in an ingroup context.…”
Section: Implications For Displaced Revenge Researchsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings extend the literature on displaced revenge (Sjöström et al, 2018;Strenstrom et al, 2008) in several ways. First, they show that group-directed displaced revenge occurs in an ingroup context.…”
Section: Implications For Displaced Revenge Researchsupporting
confidence: 91%
“…Participants were randomly assigned to one of four conditions in a 2 Group Embodiment (low vs. high) × 2 Offender Status (boss vs. co‐worker) between‐subjects design. We instructed participants to imagine that they were the victim of a workplace transgression (loosely based on Sjostrom et al., 2018) that resulted in severe negative personal consequences (e.g., public humiliation; Appendix ). We held unforgiveness towards the offender constant in all conditions by stating that the victim ‘did not forgive and viewed the offender's behaviour as inexcusable’.…”
Section: Methodsmentioning
confidence: 99%
“…This finding has now been replicated in a number of studies conducted in different contexts, with different methodological approaches, and different types of offender feedback (e.g., Funk et al, 2014; Gollwitzer et al, 2014; Gollwitzer & Denzler, 2009; Sjöström et al, 2018; Sjöström & Gollwitzer, 2015). Together, these studies demonstrate that punishment followed by offender feedback is particularly beneficial for victims when victims perceive that punishment effected a “moral change” in the offender, that is a positive change in the offender’s moral attitude toward their wrongdoing (Funk et al, 2014).…”
Section: Empowerment-focused Theories Of Punishment and Revengementioning
confidence: 75%
“…Existing findings have shown that victims of previous injustice or mistreatment tend to pay the same act forward, hurting innocent people who were not involved in the initial interaction (e.g. Gray et al, 2014; Strang et al, 2016), and ‘displaced revenge’ towards an innocent person can be especially satisfying when the transgressor and the displaced target belong to a group that is perceived as highly entitative (Sjöström & Gollwitzer, 2015; Sjöström et al, 2018). Our studies systematically examined how observers morally evaluate a person's act of paying forward the previous mistreatment, a moral judgement perspective that has not received enough attention in previous research.…”
Section: Discussionmentioning
confidence: 99%